Climate Change, Millet and Ritual Relationship with the Magars of Argal, Baglung, Nepal - Khattri, Man Bahadur (Dhaulagiri Journal of Sociology and Anthropology, 2013)
This paper focuses on cultural analysis and how people are coping with new situation created by climate change in production of millet. Changes relating to climate change are observed; perceived and understood on a local level. This is an important area of study for anthropologists and it is interest of climate scientists as well. This paper is based on anthropological analysis on climate change effects on finger millet production in Argal VDC of Baglung district, West of Nepal. Millet is a staple food of people of Argal and most of Hill people of Nepal. Millet is not only staple food and associated with nutrition of people. It's also associated with rituals during production and as well as during consumption. Increasing temperature, changing rainfall patterns, extreme weather events are linked with climate change which has direct effect on life of all people but also millet production and ritual activities. DOI: http://dx.doi.org/10.3126/dsaj.v6i0.8481 Dhaulagiri Journal of Sociology and Anthropology Vol. 6, 2012 107-124